BDNF Val66Met polymorphism as a moderator of exercise enhancement of smoking cessation treatment in anxiety vulnerable adults. (March 2016) - Smits, Jasper A.J.; Powers, Mark B.; Rosenfield, David; Zvolensky, Michael J.; Jacquart, Jolene; Davis, Michelle L.; Beevers, Christopher G.; Marcus, Bess H.; Church, Timothy S.; Otto, Michael W.
Abstract: Background: Exercise interventions facilitate the odds of quit success among high-anxiety sensitive adults smokers. We examined the dependency of these benefits on the genetic BDNF Val66Met (rs6265) polymorphism; individuals who are Met carriers have lower BDNF responses and reduced associated benefits from exercise. Accordingly, we hypothesized that the efficacy of vigorous-intensity exercise for smoking cessation would be specific to high-anxiety sensitive Val/Val carriers. Methods: Participants were adults ( N = 55) of European ancestry who had participated in a randomized controlled trial comparing a smoking cessation program augmented with exercise vs. augmented with a wellness control treatment. In this secondary analysis, growth curve models for point-prevalence abstinence (PPA) and prolonged abstinence (PA) employed for the main outcome analyses were amended to test the moderator effects of the BDNF Val66Met polymorphism. Results: Consistent with prediction, the advantage of exercise over control for PPA was significantly greater among high-anxiety sensitive persons with the Val/Val genotype than for those with the Val/Met genotype. This advantage did not reach statistical significance for PA. Differences in abstinence between the exercise and control interventions among low-anxiety sensitive smokers were not dependent on the BDNF Val66Met polymorphism. Conclusions: We found that the efficacy of exercise for augmenting smoking cessation treatment is intensified among high-anxiety sensitive smokers who are Val/Val carriers. This observation is consistent with findings documenting BDNF mediation of exercise benefits and greater negative affect among smokers who are Val/Val carriers. These data encourage further evaluation of the association between the BDNF polymorphism, exercise, anxiety sensitivity, and smoking cessation. Highlights: Exercise facilitates the odds of smoking cessation among high-anxiety sensitive adults. BDNF Val66Met polymorphism may moderate this effect. Findings may represent progress toward precision medicine.